Reinforcing earth foundations with geosynthetic materials - Ponomarev Andrey Budimirovich; Ivanova Tatiana Viktorovna (E3S Web of Conferences, 2023)
The article gives key terms and definitions of geosynthetic materials currently used in construction, namely for reinforcement of earth foundations. Primary functions and types of geosynthetic materials are shown. Most part of the article is dedicated to the results obtained by various researchers. Reinforcement by geosynthetic materials is described for sandy and loamy soils, soil bedding, fiber soil, karsted soil, and using geosynthetics in mollisols.